The awareness and understanding of Islamic economy among accountancy students in UiTM Puncak Alam / Muhammad Nor Syafiq Abdullah - Abdullah, Muhammad Nor Syafiq (Academy of Contemporary Islamic Studies (ACIS), 2018)
Islam is a universal, integrity, and comprehensive life system that had set a perfect journey for human life. As a way of life, Islam touches all matters pertaining to life, from the simplest to the most complex of affairs. Both in the political, economic, educational, artistic, social, cultural, and another aspects. Islam is the perfect religion, governing economic matters. When the economy of a country or national economy that applies the basis of the Qur'an and Hadith is used as the ultimate guide, surely the economy of a country will go well and avoid the contradictory things of syarak. The fact is not all Islamic countries in the world are implementing sharia-compliant economic policies in their economic systems. But, some countries still practice conventional economic systems that have many advantages but bring harm to Muslims. So, people nowadays must know about economic system in our country. They also can choose to use the system that is proper for them to apply in their economy system. They generate national income through conventional economic system which they have practiced since time immemorial. This is quite difficult for them to continue to use the Islamic economic system if not given understanding exactly about the advantages contained in the economic system of Islam when they use it.